THE PHILOSOPHY OF SCIENCE. A DELINEATION OF ITS SCOPE AND BOUNDARIES - Obi-Okogbuo, Jerry (European Scientific Journal, ESJ, 2015)
There is currently going on in our institutions of higher learning a worrisome conflation of the philosophy of science with some other areas of research especially the history of science, the sociology of science and science education. There are a number of reasons for this anomaly. The most pathetic is the conflation done because of lucre: the sordid material or pecuniary gain to be made from doing so. Sometimes the conflation arises from the confusion of a task of the philosophy of science to foster the unity of the sciences. Practitioners of such other sciences often tend to conflate the philosophy of science and the science. Sometimes the conflation arises from confusing the philosophy of science with its essential tool, the history of science. Historians of science often conflate philosophy of science and history of science. I suspect, however, that the more serious reason for most of the conflations is ignorance of the philosophy of science as a discipline on its own right. Whatever the reason for the conflation, this paper as the theme states, has the objective to delineate the scope and boundary of the philosophy of science and this implies establishing the objects, methodology and definition of the philosophy of science. This paper fills the need to present the philosophy of science as a distinct discipline, standing on its own rights, which does not need to be fused with any other discipline.